Hubungan Filsafat dengan Ilmu Pengetahuan dan Relevansinya Di Era Revolusi Industri 4.0 (Society 5.0) - Fadli, Muhammad Rijal (Jurnal Filsafat "WISDOM", 2021)
Philosophy and science are human efforts in understanding the concepts and methods of a scientific discipline. The changing times and developments have ushered the philosophy of a configuration by showing how the "tree of knowledge" grows and branches fruitfully from each of the disciplines, to break away from the trunk of its philosophy, develop and follow its methodological trends. This research method uses the hermeneutic method in explaining the reality that occurs with elements of interpretation and description. The results of the research can be described that the study of the relationship between philosophy and science has progressed so intensely. Philosophy and science are indispensable for their presence during the development of science and technology which is marked by the sharpening of scientific specialization, because by studying philosophy scientists are expected to be aware of their limitations so as not to be trapped into intellectual arrogance. It is impossible to counter-discourse developing science and technology, but rather to reduce the negative impact of the technology itself. In the era of the industrial revolution 4.0 and Society 5.0, the community groups are very heterogeneous, so it is very risky to the problems faced regarding the development of technology and can change the mindset of life into a more sophisticated pattern of life with the power of technology such as robots and the internet. So the science that is used as an axiological milestone in directing and controlling the development of science and technology in a positive way for the benefit of mankind and its environment is philosophy and science.Â